Analisis Prakiraan Kebutuhan Energi Listrik Tahun 2015-2024 Wilayah Pln Kota Pekanbaru Dengan Metode Gabungan - Muhammad Bobby Fadillah; Dian Yayan Sukma; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Forecast of electrical energy needs in PLN Pekanbaru region in the next 10 years using a combined method is a method formulated by combining several methods such as analysis methods, econometric methods, and trend methods, with sectoral approaches is grouping PLN’s customers into four groups of sectors (house hold, commercial, public, and industrial). This forecast is based on the growth of energy consumption and economic growth. The data used is the historical data from 2001 to 2014. The results forecast of total electric energy needs from year 2015 to 2024 is 9.96% per year with energy needs in 2015 is 1899.99 GWh grow into 4466.52 GWh on 2024 while the peak load Pekanbaru City is 281.68 MW in 2015 and grew into a 662.18 MW in 2024.Keywords: forecasting energy needs, peak load, the trend